Fate and behaviour of veterinary sulphonamides under denitrifying conditions - Bílková, Zuzana; Malá, Jitka; Hrich, Karel (The Science of the total environment, 2019)
Antibiotics are among the most widely administered drugs in the growing animal food industry. Of all the antibiotics approved for agriculture, sulphonamides are of particular interest. Their spectrum of activity is broad, affecting gram-positive, gram-negative, and many protozoal organisms, and they have been used for the treatment of a wide variety of animals. Animal manure is one of primary sources of soil contamination by sulphonamides. As they have a low soil sorption potential and are therefore highly mobile in soil, they can be transported to groundwater. In the present study, papers dealing with the fate and behaviour of veterinary sulphonamides under denitrifying conditions often arising in the subsurface are reviewed. Veterinary sulphonamide-exposed conditions can result in either inhibition or stimulation of the denitrification process owing to their toxicity or stress for denitrifiers. The effect of sulphonamides on individual denitrification steps is unbalanced, which can cause accumulation of process intermediates (dinitrogen oxide, nitrites). Although research results related to veterinary sulphonamide biodegradation in a nitratereducing environment show great variety, they indicate that these compounds are biodegradable under denitrifying conditions, that their biodegradation fits the first-order kinetics model, and that microbial action is the main mechanism of their dissipation. Regarding biodegradation pathways, research to date has only focused on sulfamethoxazole. Its degradation is driven by the presence of nitrous acid, which is formed from nitrites generated by the denitrification process as an intermediate product. Nevertheless, sulfamethoxazole degradation is abiotic, meaning that it does not participate in the denitrifying metabolism. For the formation of sulfamethoxazole transformation products, including its nitro, nitroso and desamino derivatives, the presence of the primary aromatic amine group is key. As this functional group is common for all sulphonamides, it can be assumed that these transformation products are also involved in the degradation pathways of other sulphonamides.
Keywords: Antimicrobial; Sulfanilamide; Anti-Bacterial Agents; Denitrification; Agriculture; Biodegradation, Environmental; biodegradace; Suphamethoxazole; zemědělství; sulfonamidy; chemické látky znečišťující vodu; Sulfamethoxazole; sulfamethoxazol; Water Pollutants, Chemical; Sulfonamides; denitrifikace; antibakteriální látky; Antibiotic; Nitrate-reducing environment; Groundwater; Soil; sulfanilamid